Situation Report: Romania, 29 January 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's Personality Cult Abroad Ceausescu Celebrates His 65th Birthday Mu'ammar al-Qadhafi [Muammar Qaddafi] Visits Romania A Romanian View of the World Economic Crisis The Elderly in Romania Problems with Irrigation More Failures in Environmental Protection